2021
DOI: 10.5937/scriptamed52-31191
|View full text |Cite
|
Sign up to set email alerts
|

Onset rate and intensity of signs of organophosphate poisoning related to paraoxon dose and survival in rats

Abstract: Introduction: Oganophosphorus compounds (OP) bind to acetylcholinesterase (AChE) and inactivate it. In the synaptic cleft, undestroyed and accumulated acetylcholine produce the acute cholinergic effects. The aim of this study was to determine the frequency, speed of onset and intensity of certain signs of paraoxon poisoning depending on dose and outcome of poisoning. Methods: The study was conducted in adult Wistar rats. The median lethal dose (LD50) of paraoxon as well as protective ratio (PR) of atropine (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…e choice of studying acetylcholinesterase inhibitory potential of the identi ed metabolites was informed because of the piloerection, tremor, and lacrimation observed following administration of KWAPF01. ese observations are some of the clinical signs of acetylcholinesterase inhibition, as reported by Maksimović et al [27]. AChE is a cholinergic enzyme found primarily at postsynaptic neuromuscular junctions in muscles and nerves [28].…”
Section: Discussionmentioning
confidence: 62%
“…e choice of studying acetylcholinesterase inhibitory potential of the identi ed metabolites was informed because of the piloerection, tremor, and lacrimation observed following administration of KWAPF01. ese observations are some of the clinical signs of acetylcholinesterase inhibition, as reported by Maksimović et al [27]. AChE is a cholinergic enzyme found primarily at postsynaptic neuromuscular junctions in muscles and nerves [28].…”
Section: Discussionmentioning
confidence: 62%
“…No clear relationship was found between the intensity of dyspnoea and the dose of paraoxon. However, in the recent study, a clear relationship was found between the onset rate of dyspnoea, as well as the overall intensity of dyspnoea and lethal outcome of poisoning (29). Respiratory failure is a consequence of both peripheral and central cholinergic effects (30).…”
Section: Discussionmentioning
confidence: 98%
“…Paraoxon (diethyl (4-nitrophenyl) phosphate) is the active metabolite of the OP insecticide parathion. 13 The phosphorothioates (P=S) (eg, diazinon, parathion) are more lipophilic than phosphates (P=O) (eg, dichlorvos, paraoxon). Spontaneous reactivation of dimethyl-phosphorylated AChE often occurs rapidly even without oxime therapy.…”
Section: Discussionmentioning
confidence: 99%